La ardilla listada - Whitehouse, Patricia, 1958-; Abello, Patricia (Chicago, Ill. : Heinemann Library, 2004)
Discusses the physical characteristics and habits of chipmunks, as well as their underground homes.
Includes index.
Accelerated Reader
Keywords: Chipmunks -- Juvenile literature